Integration of Tunable Optical Delay Line Filter for Dispersion Management in a Fiber-FSO Architecture - SOWMYAA VATHSAN, M. S.; PRAKASH, P.; KASTHURI, P.; SASITHRADEVI, A. (Advances in Electrical and Computer Engineering, 2025)
Mobile networks have been expanding over the years with high-capacity and highly scalable optical transport systems. These systems are designed to help network operators handle the increasing data traffic demands and support the deployment of advanced technologies like 5G, IoT and provide services, such as online learning, social media platforms and telemedicine. Radio-over-fiber (RoF) and microwave photonics technology enable efficient transmission and delivery of high-capacity data traffic in fronthaul networks with minimal signal loss and dispersion. This study presents a reliable Fiber-Free Space Optics (FSO) hybrid architecture incorporating a tunable optical delay line filter (DLF) for dynamic dispersion compensation. The proposed fiber-FSO architecture enhances the signal quality and compensates dispersion up to ±106 ps/nm in the optical link. This architecture has been analyzed for various climatic conditions such as clear weather (CA), light fog (LF), moderate rain (MR), and heavy rain (HR). The results show that using the DLF enhances receiver sensitivity by about 1.5 dB in all weather conditions, making the system more reliable for high-speed optical communication.